Implementasi Program Mobil Pustaka Keliling dalam Meningkatkan Minat Baca Siswa-Siswi di Kabupaten Bintan - Ananda, Almar; Nur Kahana, Kartini; Sholeh, Chaereyranba (Policy, Law and Political Research Center, 2023)
This study aims to find out how the implementation process is found in the Implementation of the Mobile Library Car Program in Increasing Students' Interest in Reading in Bintan Regency. This type of research was conducted using qualitative research methods with a descriptive approach. The location of this research was carried out at the Bintan Regency Regional Library and Archives Service. Data collection was carried out using purposive sampling method. Data obtained through primary data and secondary data. Data validity test was carried out by source triangulation and analyzed. The results and discussion show that the implementation of the mobile library car program in increasing students' interest in reading has been running in accordance with standard operating procedures using implementation indicators, namely, policy standards and objectives, resources, characteristics of implementing organizations, attitudes of implementers, inter-organizational communication, social, economic and political environment.